Sodium ion battery binder and sodium ion battery using same
By using sulfonated polyether sulfone as a binder in sodium ion batteries, the problem of easy gelation of the positive electrode slurry is solved, and the specific energy of the battery and the stability of the electrode structure are improved.
Patent Information
- Application Number
- CN202411673667.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-22
AI Technical Summary
The positive electrode slurry of sodium ion battery is easily gelled, resulting in unstable electrical performance of the battery cell.
The sulfonated polyether sulfone is used as the binder for sodium ion batteries, and its sulfonated acid groups can neutralize the residual alkali on the surface of the positive electrode material, thereby forming a more stable positive electrode slurry.
It effectively prevents slurry gelation, improves the specific energy of the battery and the stability of the electrode structure, and improves the overall performance of the battery.
Smart Images

Figure BDA0005146526880000021 
Figure BDA0005146526880000071 
Figure BDA0005146526880000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery binder and a sodium ion battery using the binder. Background Art
[0002] With the continuous development of industrialization and urbanization, human demand for energy continues to increase. The resource reserves of traditional energy sources such as oil, coal, and natural gas are limited, and they will also bring a series of environmental problems, such as the emission of large amounts of carbon dioxide, which will lead to rising global temperatures and severe damage to the ecosystem. In order to reduce carbon emissions and reduce environmental pollution, new energy has gradually become the development direction to replace traditional energy and provide new kinetic energy for human production and life. Electrochemical energy storage has become a hot topic of research at home and abroad due to its advantages such as good equipment mobility, fast response speed, high energy density and high cycle efficiency. Therefore, charge-discharge chemical batteries play a leading role in the country's development of the new energy electrification era.
[0003] Lithium-ion batteries are widely used in consumer electronics, power batteries, energy storage and other fields due to their excellent comprehensive performance. However, the uneven distribution and gradual scarcity of lithium resources in the earth's crust have led to an increasing cost of lithium-ion batteries. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Both work by moving sodium ions (lithium ions) between the positive and negative electrodes. In addition, sodium is abundant in resources, has high accessibility and low cost. Therefore, sodium-ion batteries are a powerful supplement or substitute for lithium-ion batteries.
[0004] The cathode slurry plays a vital role in determining the cost, safety, specific energy and cycle life of sodium-ion batteries. Layered metal oxides have become the mainstream products of current industrialization due to their high sodium ion content, high initial capacity, high energy density and best overall performance. However, the presence of residual alkali on the surface of layered metal oxide materials will cause the conventional binder PVDF to defluorinate, resulting in gelation of the slurry. In addition, the residual alkali substances will also react with the electrolyte to generate acid, corroding the cathode slurry and thus affecting the stability of the electrical performance of the battery cell. Summary of the invention
[0005] In order to improve the gelation problem of positive electrode slurry of sodium ion batteries, the present application provides a sodium ion battery binder and a sodium ion battery using the binder.
[0006] In a first aspect, the present application provides a sodium ion battery binder, which adopts the following technical solution:
[0007] A sodium ion battery binder is a sulfonated polyethersulfone, and the structural formula of the sulfonated polyethersulfone is:
[0008] By adopting the above technical solution, the present application adopts sulfonated polyethersulfone as a sodium ion battery binder, and the sulfonic acid group on the sulfonated polyether molecular chain can effectively neutralize the residual alkali on the surface of the active material. Therefore, by adopting sulfonated polyethersulfone, a more stable sodium nickel iron manganese oxide system positive electrode slurry can be formed to improve the specific energy of the battery. Moreover, the pole piece using sulfonated polyethersulfone as a binder can still maintain a good peel strength, which can avoid the occurrence of slurry gelation from the root, and improve the problem of sodium ion battery positive electrode slurry gelation.
[0009] In a specific embodiment, the sulfonation degree of the sulfonated polyethersulfone is 20-50%.
[0010] By adopting the above technical solution, the present application has found through experiments that sulfonated polyethersulfone, when the degree of sulfonation is 20-50%, helps to improve the stability and ion stripping strength of the battery positive electrode sheet, further prevents the gelation of the sodium ion battery positive electrode slurry, and can improve the stability of the electrode structure.
[0011] In a specific embodiment, the sodium ion battery binder is applied to a soft pack battery.
[0012] In a second aspect, the present application provides a sodium ion battery using the above-mentioned sodium ion battery binder, adopting the following technical solution:
[0013] A sodium ion battery using the above-mentioned sodium ion battery binder, wherein the positive electrode sheet used in the sodium ion battery includes a solid material and N-methylpyrrolidone. Based on the total weight of the solid material, the solid material comprises the following raw materials in weight percentage: 3%-8% sodium ion battery binder, 3% conductive agent, and 89%-94% positive electrode active material.
[0014] By adopting the above technical solution, the binder can effectively bind the positive electrode active material, conductive agent and other components tightly together to form a stable positive electrode structure. N-methylpyrrolidone can effectively disperse the binder, conductive agent and other components to form a uniform slurry. Moreover, N-methylpyrrolidone has a low boiling point and a fast volatilization rate, which helps to control the drying process of the slurry and prevent the slurry from gelling during the drying process. Therefore, by reasonably matching the binder, conductive agent, sodium nickel iron manganese oxide positive electrode slurry and N-methylpyrrolidone, the gelation of the positive electrode slurry is effectively improved. It not only helps to improve the preparation efficiency of the battery, but also helps to improve the stability of the battery positive electrode slurry and positive electrode sheet.
[0015] In a specific embodiment, the conductive agent includes SuperP conductive carbon black and / or graphene.
[0016] By adopting the above technical solutions, SuperP conductive carbon black and graphene both have excellent conductive properties, and can form a stable conductive network in the positive electrode slurry and positive electrode sheet, which not only improves the current transmission efficiency, but also helps to maintain the stability of the positive electrode slurry and positive electrode sheet, avoiding thickness rebound of the positive electrode sheet, thereby further improving the stability of the positive electrode slurry and preventing the positive electrode slurry from gelling.
[0017] In a specific embodiment, the conductive agent includes SuperP conductive carbon black and graphene in a weight ratio of (1.6-1.9):(1.1-1.4).
[0018] By adopting the above technical solution, the weight ratio of SuperP conductive carbon black and graphene is adjusted within the above range, and the obtained positive electrode sheet has greater peel strength. This may be because, within the above weight ratio range, SuperP conductive carbon black and graphene can further improve the bonding performance of the positive electrode slurry.
[0019] In a third aspect, the present application provides a method for preparing a sodium ion battery, using the following technical solution:
[0020] A method for preparing a sodium ion battery comprises the following steps:
[0021] Dissolving a sodium ion battery binder in N-methylpyrrolidone to obtain a glue solution;
[0022] Adding a conductive agent and a positive electrode active material to the glue solution, adjusting the solid content to 50%-60%, obtaining a positive electrode slurry, and making the positive electrode slurry into a positive electrode sheet;
[0023] The positive electrode sheet, the negative electrode sheet and the separator are stacked in sequence, welded, packaged, baked, injected with electrolyte solution, re-sealed, formed and capacity divided to obtain a sodium ion battery.
[0024] By adopting the above technical solution, the sodium ion battery binder is first dissolved in N-methylpyrrolidone to obtain a glue solution, which provides a uniform bonding environment for the subsequent preparation of the positive electrode slurry. The solid content of the positive electrode slurry is adjusted to the above range, which helps the positive electrode slurry to maintain uniformity and density during the coating process, thereby improving the stability of the positive electrode sheet.
[0025] In summary, this application has the following beneficial effects:
[0026] 1. The present application adopts sulfonated polyethersulfone as a sodium ion battery binder, and the peel strength of the battery pole piece can still be maintained at a good level, which can avoid the occurrence of slurry gelation from the root and improve the problem of sodium ion battery positive electrode slurry gelation.
[0027] 2. In the present application, sulfonated polyethersulfone with a sulfonation degree of 20-50% is preferably used to further prevent gelation of the positive electrode slurry of the sodium ion battery.
[0028] 3. The method of the present application helps to maintain uniformity and density of the positive electrode slurry during the coating process, thereby improving the stability of the positive electrode sheet. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the technical solutions in the present invention will be fully described in combination with the present invention below. Obviously, the described embodiments are part of the embodiments of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0031] Example
[0032] Example 1
[0033] The present embodiment provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is made of a positive electrode slurry, the positive electrode slurry comprises a solid material and N-methylpyrrolidone, and the solid material adopts the following components in weight percentage: 5% sodium ion battery binder, 3% conductive agent, and 92% sodium nickel iron manganese oxide (NaNi1 / 3Fe1 / 3Mn1 / 3O2).
[0034] Among them, the sodium ion battery binder is a sulfonated polyethersulfone with a sulfonation degree of 30%, and the structural formula of the sulfonated polyethersulfone is: The conductive agent is a mixture of SuperP conductive carbon black and graphene in a weight ratio of 1.75:1.25.
[0035] This embodiment also provides a method for preparing a sodium ion battery, comprising the following steps:
[0036] The sodium ion battery binder is dissolved in N-methylpyrrolidone and stirred evenly to obtain a glue solution.
[0037] A conductive agent and a positive electrode active material are added to the glue solution, and the solid content is adjusted to 60% to obtain a positive electrode slurry.
[0038] The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and is baked and rolled to obtain a positive electrode sheet.
[0039] The positive electrode sheet, the negative electrode sheet and the separator are stacked in sequence, welded, packaged, baked, injected with electrolyte, re-sealed, formed and capacity divided to obtain a soft-pack battery, i.e. a sodium-ion battery.
[0040] Example 2
[0041] The only difference between this embodiment and embodiment 1 is that the solid material adopts the following components in weight percentage: 8% sodium ion battery binder, 3% conductive agent, and 89% sodium nickel iron manganese oxide (NaNi1 / 3Fe1 / 3Mn1 / 3O2).
[0042] Example 3
[0043] The only difference between this embodiment and embodiment 1 is that the solid material adopts the following components in weight percentage: 3% sodium ion battery binder, 3% conductive agent, and 94% sodium nickel iron manganese oxide (NaNi1 / 3Fe1 / 3Mn1 / 3O2).
[0044] Example 4
[0045] The only difference between this embodiment and embodiment 1 is that the sulfonation degree of the sulfonated polyethersulfone is 10%.
[0046] Example 5
[0047] The only difference between this embodiment and embodiment 1 is that the sulfonation degree of the sulfonated polyethersulfone is 20%.
[0048] Example 6
[0049] The only difference between this embodiment and embodiment 1 is that the sulfonation degree of the sulfonated polyethersulfone is 50%.
[0050] Example 7
[0051] The only difference between this embodiment and embodiment 1 is that the sulfonation degree of the sulfonated polyethersulfone is 80%.
[0052] Example 8
[0053] The only difference between this embodiment and Embodiment 1 is that the conductive agent is a mixture of SuperP conductive carbon black and graphene in a weight ratio of 1.5:1.5.
[0054] Example 9
[0055] The only difference between this embodiment and Embodiment 1 is that the conductive agent is a mixture of SuperP conductive carbon black and graphene in a weight ratio of 1.6:1.4.
[0056] Example 10
[0057] The only difference between this embodiment and Embodiment 1 is that the conductive agent is a mixture of SuperP conductive carbon black and graphene in a weight ratio of 1.9:1.1.
[0058] Embodiment 11
[0059] The only difference between this embodiment and Embodiment 1 is that the conductive agent is a mixture of SuperP conductive carbon black and graphene in a weight ratio of 2.0:1.0.
[0060] Example 12
[0061] The only difference between this embodiment and Embodiment 1 is that the conductive agent is SuperP conductive carbon black.
[0062] Embodiment 13
[0063] The only difference between this embodiment and Embodiment 1 is that the conductive agent is graphene.
[0064] Embodiment 14
[0065] The only difference between this embodiment and embodiment 1 is that a conductive agent and a positive electrode active material are added to the glue solution, and the solid content is adjusted to 50% to obtain a positive electrode slurry.
[0066] Comparative Example
[0067] Comparative Example 1
[0068] The only difference between this comparative example and Example 1 is that an equal amount of polytetrafluoroethylene is used to replace the sulfonated polyethersulfone.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that a conductive agent and a positive electrode active material are added to the glue solution, and the solid content is adjusted to 40% to obtain a positive electrode slurry.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 1 is that a conductive agent and a positive electrode active material are added to the glue solution, and the solid content is adjusted to 70% to obtain a positive electrode slurry.
[0073] Performance testing
[0074] The following performance tests were performed on the sodium ion batteries prepared in Examples 1-14 and Comparative Examples 1-3:
[0075] After the positive electrode slurry is obtained in the preparation process of the sodium ion battery, it is allowed to stand, and the viscosity of the positive electrode slurry is tested after standing for 0 h, 1 h, 2 h, and 24 h.
[0076] The viscosity change of the positive electrode slurry in the preparation process of the sodium ion battery is detected to see whether it exceeds 1000mPa·s during the period of standing for 0-24h. When the viscosity change exceeds 1000mPa·s, it means that the positive electrode slurry rebounds after 24h, and the stability of the positive electrode slurry and the positive electrode sheet is poor.
[0077] Detect the peel strength of the positive electrode sheet during the preparation process of sodium ion batteries.
[0078] The test results are shown in Table 1.
[0079] Table 1
[0080]
[0081]
[0082] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that compared with Example 1, Comparative Example 1 showed gelation, and the positive electrode sheets in the sodium ion battery preparation process of Comparative Examples 2-3 rebounded after 24 hours, which shows that a stable positive electrode slurry can be formed by adopting the raw material ratio and process conditions of Comparative Example 1. Under the same ratio of positive electrode slurry, sulfonated polyethersulfone is used as a binder, which can make the positive electrode sheet maintain good peel strength.
[0083] Combining Examples 1-14 and Table 1, it can be seen that the positive electrode sheets in the sodium ion battery preparation process of Examples 4 and 7 rebounded after 24 hours, and the positive electrode sheet peeling strength of Examples 8, 12, and 13 was less than 220N / m. The sulfonation degree of sulfonated polyethersulfone of Examples 4-7 gradually increased, and the positive electrode sheet peeling strength of Example 4-6 gradually increased, but the positive electrode sheet peeling strength of Example 7 was less than that of Example 6. The amount of SuperP conductive carbon black in the conductive agent of Examples 8-11 gradually increased, and the positive electrode sheet peeling strength of Examples 8-10 gradually increased, but the positive electrode sheet peeling strength of Example 10 was less than that of Example 9. This shows that the use of sulfonated polyethersulfone with a sulfonation degree of 20-50%, SuperP conductive carbon black and graphene with a weight ratio of (1.6-1.9): (1.1-1.4) can help to further improve the stability and bonding performance of the positive electrode sheet.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A sodium ion battery binder, characterized in that: It is sulfonated polyethersulfone, and the structural formula of the sulfonated polyethersulfone is:
2. A sodium ion battery binder according to claim 1, characterized in that: The sulfonation degree of the sulfonated polyethersulfone is 20-50%.
3. An application of the sodium ion battery binder according to claim 1 or 2, characterized in that: The sodium ion battery binder is applied to soft-pack batteries.
4. A sodium ion battery using the sodium ion battery binder according to claim 1, characterized in that: The positive electrode sheet used in the sodium ion battery includes solid materials and N-methylpyrrolidone. Based on the total weight of the solid materials, the solid materials have the following weight percentages of raw materials: 3%-8% sodium ion battery binder, 3% conductive agent, and 89%-94% positive electrode active material.
5. A sodium ion battery according to claim 4, characterized in that: The conductive agent includes SuperP conductive carbon black and / or graphene.
6. A sodium ion battery according to claim 5, characterized in that: The conductive agent includes SuperP conductive carbon black and graphene in a weight ratio of (1.6-1.9):(1.1-1.4).
7. A method for preparing a sodium ion battery according to any one of claims 4 to 6, characterized in that: The steps include: The sodium ion battery binder is dissolved in N-methylpyrrolidone to obtain a glue solution; Adding a conductive agent and a positive electrode active material to the glue solution, adjusting the solid content to 50%-60%, obtaining a positive electrode slurry, and making the positive electrode slurry into a positive electrode sheet; The positive electrode sheet, the negative electrode sheet and the separator are stacked in sequence, welded, packaged, baked, injected with electrolyte solution, re-sealed, formed and capacity divided to obtain a sodium ion battery.